Homestay Planning and Development in Belawa Tourism Village, Cirebon Regency - Chondro Suryono; Abdul Khalim (Jurnal Toursci, 2026)
Background. The development of tourist villages requires supporting facilities that can improve the quality of the tourist experience while providing economic benefits to the local community. One of the facilities that has a strategic role is homestay as a form of community-based accommodation. Purpose. This study aims to analyze homestay planning in supporting the development of Belawa Tourism Village, Cirebon Regency, as well as identify obstacles faced in its implementation. Method. This study uses a qualitative descriptive approach with data collection techniques through observation, in-depth interviews, and documentation. Informants were selected using purposive sampling techniques involving the village government, Tourism Awareness Groups (Pokdarwis), communities, and related stakeholders. Data analysis is carried out descriptively through the process of data reduction, data presentation, and drawing conclusions. Results. The results of the study show that Belawa Tourism Village has great potential in homestay development because it is supported by Belawa turtle conservation tourism attractions, local cultural arts, agro-tourism, and fairly high community participation. Homestay planning has referred to the principles of the ASEAN Tourism Strategic Plan (ATSP), including aspects of hosts, homestay providers, accommodation standards, tourism activities, partnerships, and sustainability. However, its implementation still faces various obstacles, including low public understanding of homestay management, the lack of clear regulations, limited human resources and funding, lack of training, and lack of optimal partnerships with the government and tourism industry. Conclusion. Therefore, it is necessary to strengthen community capacity through training, the preparation of operational standards for homestay management, increased multi-stakeholder collaboration, as well as policy and financing support so that the development of homestays can increase the competitiveness of Belawa Tourism Village in a sustainable manner.